EDITORIAL - Ivan Čuk (University of Ljubljana Press (Založba Univerze v Ljubljani), 2021)
Dear friends, All gymnastic disciplines were excellent at this year's Summer Olympic Games. Great achievements of our athletes in artistic gymnastics, rhythmic gymnastic and trampolining! From my subjective point of view, Nikita Nagorny made a huge step forward to further our sport. It took all this time since OG 1988 in Seoul, when Valery Ljukin from the former Soviet Union performed a triple salto backward tucked, to see Nikita Nagorny perform a triple salto backward piked at a major competition. It will take some more time before followers start performing the triple backward piked. However, our science supports and facilitates improvements in apparatus, the development of better methods of strength training, psychological readiness, and so on, and all this leads to further developments in our sport. Having the Olympic Games and the World Championships within three months of the same year created many challenges for everyone involved in competitive gymnastics. On one hand, there is gymnasts' tiredness, on another, new faces bring in new energy. There are new challenges for researchers too. In the middle of October, Flavio Bessi organised International Freiburg Gymnastics Congress online. You can find it at https://www.sport.uni-freiburg.de/en/events/international-gymnastics-congress. Contributing authors in this issue are from Tunisia, Oman, Brazil, Germany, United Kingdom, Slovenia, Russia and Greece. Again, many different aspects of gymnastics are presented. Anton Gajdoš and Michal Babela drafted the 22nd short historical note introducing Samulel Piasecky from Slovakia. Sadly, we lost a gymnastic friend. Aljoša Demjanov who competed for Russia and Croatia passed away last summer. R.I.P., Aljoša. Just to remind you, if you cite the journal, its abbreviation in the Web of Knowledge is SCI GYMN J. I wish you enjoyable reading and many new ideas for research projects and articles. Ivan Čuk Editor-in-Chief